Higher education in an era of complexity: "The tributaries project" as a higher education heterotopia - Hurst, A.M.; Du Plooy, B. (South African Journal of Higher Education, 2021)
Widespread calls to develop modes of teaching and learning in higher education for a paradigm of complexity recognize higher education’s double task; namely, to graduate students not only with technical/theoretical expertise, but also the capacity for responsible citizenship. In this article we offer retrospective, philosophical reflections on a South African university engagement project, “The Tributaries Project” (2019). These reflections aim to show that such academic engagement projects, formed as “higher education heterotopia” (a concept co-opted from a 1967 lecture by Michel Foucault) are favourable sites for the second aspect of higher education’s task; that is, to foster responsible citizenship among university staff, students and graduates in an era of complexity. Further, Edgar Morin’s “seven complex lessons” detail the essential elements of this task, and by extension heterotopic spaces, such as those configured by The Tributaries Project offer ideal conditions for the implementation of Morin’s insights. In Part One, we reflect on key theoretical assumptions underlying “The Tributaries Project”, via the lens of the concept “heterotopia”. Part Two is organised by Edgar Morin’s “seven complex lessons”, with brief indications of how these lessons were implemented via the project’s diverse activities. We hope that sharing insights gained from theorizing, creating and implementing this project may inspire similar projects.